ANALISIS EFEKTIVITAS PEMANFAATAN PEMBIAYAAN PADA SEKTOR PERTANIAN DAN PENDAPATAN USAHATANI PADI DI KSPPS BMT ASSYAFIIYAH BERKAH NASIONAL CABANG KOTA GAJAH KABUPATEN LAMPUNG TENGAH - Aini, Eliza Nur; Lestari, Dyah Aring Hepiana; Rahmalia, Dian (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2025)
This study aims to analyze the effectiveness of agribusiness financing utilization, rice farming income, as well as the effect of financing utilization effectiveness and types of financing on rice farming income. The study was conducted using a survey method. The research was carried out at KSPPS BMT Assyafiiyah Berkah Nasional, Kota Gajah Branch, Kota Gajah Regency, Central Lampung. The number of respondents consisted of 47 recipients of mudharabah financing and 45 recipients of musyarakah financing. Data collection was conducted from January to February 2025. The level of financing utilization effectiveness was analyzed using quantitative descriptive methods, farming income was analyzed by calculating the R/C ratio, and the influence of financing utilization effectiveness and financing type on rice farming income was analyzed using multiple regression analysis. The results of the analysis show that the effectiveness of financing utilization in the agricultural sector at KSPPS BMT Assyafiiyah Berkah Nasional, Kota Gajah Branch is categorized as very effective for mudharabah financing and effective for musyarakah financing. The average financing utilization reached 80.7 percent for mudharabah and 79.8 percent for musyarakah. The income generates from the first planting season of rice farming  under mudharabah financing amounted to IDR 22,224,128.01 per hectare, while the income from cash costs under musyarakah financing amounted to IDR 22,972,311.67 per hectare, with an R/C ratio greater than 1 for rice production. The effectiveness of agricultural sector financing utilization has a positive effect on rice farming income, while the type of financing has no significant effect on rice farming income.   Key words: financing effectiveness, income, sharia cooperatives